Quid pro quo CSR and trade liberalization in a bilateral monopoly - Shih-Shen Chen; Chien-Shu Tsai; Chen Chen (Games, 2022)
We construct a dynamic bilateral monopoly game to analyze the bargaining between a foreign manufacturer and a domestic retailer regarding the wholesale price and explain the foreign upstream firm's corporate social responsibility (CSR) initiative and its economic impacts on the domestic market. Under free trade, the foreign upstream firm's CSR initiative realizes improvements in consumer surplus and social welfare in the home country. A 'win-win-win' strategy exists, as the foreign manufacturer has more of an incentive to implement CSR when the government implements a strategic trade policy. The consumer-friendly action implemented by the foreign upstream firm leads to adequate consumer welfare and social welfare, which mitigates the government's political hostility. With the high bargaining power of the foreign upstream firm and the low weight of the consumer-friendly upstream firm, the government should set a higher tariff rate for the foreign upstream firm to extract rent and enhance social welfare.
Keywords: F13; L11; L81; M14; 330; bargaining; corporate social responsibility; trade policy; vertical market